Long Relationship of Suffering with Knowledge of Handling Hyperglycemia in Sufferers Type 2 Diabetes Mellitus in the Work Area Suwawa Health Center - Fira Destiany Karama; Ita Sulistiani; Ibrahim Suleman (Universitas Muhammadiyah Palu, 2026)
Type 2 diabetes mellitus is a chronic disease that requires long-term management and is at risk of causing acute complications such as hyperglycemia. The treatment of hyperglycemia depends not only on medications, but also on the patient's knowledge in managing the disease. This study aims to determine the relationship between the length of suffering and the knowledge of handling hyperglycemia in patients with type 2 diabetes mellitus in the working area of the Suwawa Health Center. This study uses a descriptive design correlative with a cross sectional approach. The total sample was 75 respondents who were selected using the Proportional Simple Random Sampling technique. The results showed that 44 people (58.7%) of respondents who had suffered for a long <time for 5 years (58.7%), the majority had less knowledge (49.3%), while 7 people (9.3%) were knowledgeable. Respondents with a 5-year ? of suffering were 31 people (41.3%), most of them had good knowledge (40.0%), and only 1 person (1.3%) was poorly knowledged. Based on the spearman rank test, a value of p = 0.000 (p < 0.05) was obtained, so that there was a significant relationship between the length of suffering and the knowledge of hyperglycemia management in patients with type 2 diabetes mellitus in the work area of the Suwawa Health Center. It is hoped that health facilities can improve education from the beginning of diagnosis and maintain continuous education programs so that patient knowledge continues to develop.